The assisted jump squat: An alternative method for developing power in adolescent athletes - Kilgallon, M.; Beard, A. (Strength and Conditioning Journal, 2010)
The assisted jump squat can provide a safe and effective means of increasing lower limb power in conjunction with traditional training methods. Band assistance may also shift the movement specifity profile of the jump squat exercise closer to actual sporting movements by increasing movement velocities attained.